2015
DOI: 10.1002/ejic.201500174
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Ligand Properties of N‐Heterocyclic Carbenes from 77Se NMR Parameters

Abstract: The 1 J CSe coupling constants for a range of NHC-selenium adducts have been measured and used to establish a correlation with the σ-donor strength of the respective carbenes. For the subclass of amido-carbenes, the 1 J CSe values revealed a high donor capacity, very much in contrast to what the DFT-calculated HOMO energies suggest. The 1 J CH coupling constants for the C-2 atoms in azolium-type NHC precursors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
258
2
8

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(280 citation statements)
references
References 90 publications
12
258
2
8
Order By: Relevance
“…The Ag atom is in an almost linear arrangement between the two (8) is also in line with the coordination to transition metals. 37 It was found that poor σ-donors reveal high coupling constants for the C-H bond, which can be explained by a higher s-orbital character of the corresponding C-H bond 38 25[OTf ] is extremely sensitive and decomposes readily in solution which prevents its isolation. S2.10 †).…”
Section: Resultsmentioning
confidence: 99%
“…The Ag atom is in an almost linear arrangement between the two (8) is also in line with the coordination to transition metals. 37 It was found that poor σ-donors reveal high coupling constants for the C-H bond, which can be explained by a higher s-orbital character of the corresponding C-H bond 38 25[OTf ] is extremely sensitive and decomposes readily in solution which prevents its isolation. S2.10 †).…”
Section: Resultsmentioning
confidence: 99%
“…In 2013, Ganter presented the 77 Se NMR chemical shift of the respective selenoureas as a suitable probe to determine directly the π-influence of the carbene [4243], as the paramagnetic shift tensor has the largest influence on the 77 Se NMR chemical shift. This method is so far redundant [44] to the method of determining the 31 P NMR chemical shifts of the respective NHC–phosphinidene adducts [4546]. …”
Section: Introductionmentioning
confidence: 99%
“…However, the correlation coefficient with the electron donating indices TEP is worse (R 2 = 0.833). 262 An improved correlation of -electron donation with the NMR coupling constant 1 JCSe has been reported. 262 However, the data for this index are considerably scarcer than those for the chemical shifts of 31 Р and 77 Se.…”
Section: 251mentioning
confidence: 98%
“…262 An improved correlation of -electron donation with the NMR coupling constant 1 JCSe has been reported. 262 However, the data for this index are considerably scarcer than those for the chemical shifts of 31 Р and 77 Se. Obviously, the chemical shift of 77 Se, as well as other NMR indices, are under the influence not only of electronic but also anisotropic shielding effects.…”
Section: 251mentioning
confidence: 98%
See 1 more Smart Citation